P II – 3–1 Occurrence of airborne fungal spores diversity and allergenicity in two southwestern states of nigeria. (18th March 2018) - Odebode, Adeyinka; Adekunle, Adedotun; Stajich, Jason
Abstract : Background/aim: Airborne microorganisms have been shown to vary throughout the day and season depending on various environmental factors such as: type of vegetation, air pollution human activities meteorological and seasonal climatic factors. Methods: Sedimentation plate technique using Dichloran Glycerol −18 agar and Potato Dextrose Agar (culture dependent) was employed. Identification and characterisation of fungal species was carried out by amplification of internal transcribed spacer 1 and 4 gene followed by quantification of allergenic gene by reverse transcriptase quantitative polymerase chain reaction in the most abundant fungal isolates. Furthermore, the extracts obtained were analysed using SDS-PAGE to separate the fungal antigenic proteins. Molecular markers were scored manually for presence or absence of each band in the SDS-PAGE analysis. Data obtained were analysed (ANOVA) using SAS (version 9.1). Means were separated using the Duncan Multiple Range Test at p≤0.05. Linear regression analysis was done by PAST software. Results: A total of 44 fungal species were isolated from all locations sampled, Aspergillus, Penicillium and Fusarium were the most abundant and frequently surveyed fungal species in the environments while Absidia, Curvularia and Mucor had the least values of spore count in all locations. The mean relative gene expression values ranged from 18.95–31.28 for Actin, 17.38–26.77 for β tubulin and 19.74–30.63 for P. oxalicum and 30.22–37.56 for P. citrinum genes. SDS-PAGE analysis revealed a total of 25 protein bands with molecular weight between 5 and 100 kDa. A. favus had the maximum number of protein band while P. citirinum had least.It was observed that spore count in the dry season was significantly less than that of the wet season. Farm settlement had higher fungal load than other place Conclusion: This study has confirmed that production of fungal spores is indicative of weather parameters. Environmental conditions such as relative humidity (RH), temperature and wind velocity exert a significant effect on the type of population and the amount of microorganisms in the air therefore airborne microbial quantity and quality can vary with time of the day, year and location.